Biostatistical Knowledge and Training in Neonatal-Perinatal Medicine Fellowship: A National Needs Assessment of Fellows and Early Career Faculty - Jeanne Alexandra Krick; Margarita M Vasquez; Deirdre O'reilly; Nicole Lock; Megan Gray (American Journal of Perinatology, 2026)
Objective: This study aimed to assess the experiences of NPM fellows and early career neonatologists with biostatistics education during fellowship training and to evaluate their confidence in using common biostatistical methods. Study Design: This was an observational cross-sectional survey study of U.S.-based NPM fellows and early career faculty. The survey instrument was designed to assess confidence in various biostatistical techniques and training experience. The anonymous survey was distributed to members of the ONTPD and TECAN listservs in September 2022 and responses were recorded in REDCap. Results: There were 148 responses to the survey, with 87 (59%) of those being current fellows and 61 (41%) early career faculty. Only 16 (11%) respondents felt their biostatistical training was adequate for their scholarly work and future career, while 57 (38%) felt it was inadequate to meet their needs, and 50 (34%) felt it met just their basic needs. Most respondents reported being at a novice or beginner level for most biostatistical techniques. Despite many reported challenges to incorporating a dedicated curriculum into the didactic schedule, 85 (57%) felt it should be required for all NPM fellows. When comparing groups, early career faculty rated their confidence with various biostatistical techniques as higher than current fellows. There were no differences between respondents from smaller or larger programs in their evaluation of the quality of their training, access to statistical programs, or availability of mentorship. Conclusion: There are significant gaps in current biostatistical training for NPM fellows. This gap could lead to significant downstream effects in the field of Neonatology, including poor ability to assess research findings, inability to engage in meaningful quality improvement, and a lack of available mentors in the future. These gaps may be addressed by a targeted curriculum that is readily available for all NPM training programs.